Strategi Peningkatan Efektivitas Pembelajaran PAI Melalui Kurikulum Merdeka Di MTsN 3 Tambakberas Jombang - Anis indana Zulfa; Didin Sirojuddin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to analyze strategies for enhancing the effectiveness of Islamic Education (PAI) learning through the Kurikulum Merdeka at MTs Negeri 3 Tambakberas Jombang. The main focus of the research includes the planning, implementation, and evaluation of PAI learning, effective strategies that can be applied, and the obstacles and solutions faced in implementing the Kurikulum Merdeka. The research uses a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation involving the vice-principal of the curriculum, PAI teachers, and students. The findings indicate that planning involves improving teachers’ abilities through training and the development of teaching materials. The implementation of learning emphasizes differentiated instruction, the use of flexible methods, and focusing on the learning process rather than just the final result. The evaluation includes formative assessments during the learning process and summative assessments after completing the material. Effective strategies include empowering teacher communities (MGMP), periodic supervision, flexible teaching methods, training to improve teachers’ skills, and promoting religious activities to build students’ character. The main challenges identified are differences in student engagement, abilities, character, and environment, which are addressed through differentiated learning, guidance and counseling support, and the application of flexible teaching methods. This study provides practical contributions for teachers and policymakers in developing more effective PAI learning strategies and offers insights into the implementation of the Kurikulum Merdeka in a local context.